Emergence and growth of seedlings of Piscidia piscipula (L.) Sarg. under nursery conditions - Dzib Castillo, Benito Bernardo; Gonz´ález Valdivia, Noel Antonio; Carballo Hernández, José Ignacio (Acta Universitaria, 2020)
Fabaceae dominate the forests of southeastern Mexico: in the Peninsula of Yucatanthe jabín (Piscidia piscipula L.) is the dominant tree species. However, its management is poorly documented. Therefore, the objective of this work was to describe aspects of its management under nursery conditions. For this, the emergence of seedlings was evaluated after the scarification of seeds in hydrochloric acid solutions and in water at 100 °C, against others without scarification. The seedlings obtained were fertilized with the NPK (Nitrogen, Phosphorus and Potassium) formulas (17-17-17, 46-00-00 and 18-46-00) and a white control. Seedling emergence was registered for 20 days and its growth for one month, recording height and diameter. Data analysis was performed with the Kruskal Wallis non-parametric method applied in both experiments. The results did not show statistical differences between scarification treatments; the height was favored by the NPK formulas 17-7-17 and 18-46-00, whereas the largest diameter was obtained with the NPK 46-00-00 formula. This indicates that, statistically, scarification does not influence seedling emergence and that the fertilization of jabín seedlings should contain more nitrogen and phosphorous.